Religious Freedom, Religious Discrimination and the Workplace. - Vickers, Lucy R. (Hart Pub., 2008)
The book considers the extent to which religious interests are protected in the workplace, with particular reference to the protection against religious discrimination provided by the Employment Equality (Religion and Belief) Regulations 2003. It establishes a principled basis for determining the proper scope of religious freedom at work, and considers the interaction of freedom of religion with the right not to be discriminated against on grounds of religion. Discrimination on grounds of religion and belief within the workplace raises many complex and contested issues, not least because of th.